Clinical manifestation and natural history of diabetic nephropathy - Ritz, Eberhard; Zeng, Xiao-Xi; Rychlik, Ivan (Diabetes and the kidney, 2011)
The prevalence of diabetes, predominantly of type 2, and the incidence of diabetic nephropathy have dramatically increased worldwide. Diabetic patients constitute the largest proportion of patients with end-stage renal disease (ESRD) requiring dialysis or transplantation; in developed countries, this accounts for up to 50% of ESRD patients, but this proportion has stabilized and possibly somewhat decreased in recent years. Chronic kidney disease in diabetic patients is more heterogeneous than previously thought. The largest proportion suffers from proteinuric diabetic nephropathy with Kimmelstiel-Wilson lesions as the underlying pathology, but reduced glomerular filtration rate in the absence of albuminuria/proteinuria is recognized in an increasing proportion of type 2 diabetic patients. Of particular interest is the recent recognition of vascular lesions in the brain and retina as predictors of nonproteinuric nephropathy with reduced GFR; although currently unproven, such lesions may also be of potential relevance for target blood pressure. Because of the high prevalence of type 2 diabetes in the population, coexisting primary kidney disease and diabetic nephropathy occur in a sizable proportion of type 2 diabetic patients with ESRD. The optimal point to start treatment differs according to target organs. There is no doubt that in proteinuric diabetic patients the earlier the treatment (blood pressure lowering, renin-angiotensin system blockade) is started, the greater is the benefit - at least in patients with proteinuric disease and no major cardiovascular damage. In our opinion, there is no one target blood pressure that fits all patients. Survival of patients with diabetic nephropathy is to a large extent determined by cardiovascular comorbidity. It is currently a matter of debate whether the current definition of type 2 diabetes is appropriate. Some recent findings suggest that minor renal hemodynamic and morphological changes are seen even in (prediabetic) patients who fail to meet the current definition of type 2 diabetes.